2015
DOI: 10.4047/jap.2015.7.1.27
|View full text |Cite
|
Sign up to set email alerts
|

In vitrostudy of fracture strength of provisional crown materials

Abstract: PURPOSEThe purpose of this report was to evaluate the effect of the fabrication method and material type on the fracture strength of provisional crowns.MATERIALS AND METHODSA master model with one crown (maxillary left second premolar) was manufactured from Cr-Co alloy. The master model was scanned, and the data set was transferred to a CAD/CAM unit (Yenamak D50, Yenadent Ltd, Istanbul, Turkey) for the Cercon Base group. For the other groups, temporary crowns were produced by direct fabrication methods (Imiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
85
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 23 publications
10
85
0
3
Order By: Relevance
“…Therefore, direct comparison to other studies is not possible. The improved FS of CAD/CAM PMMA‐based polymers compared to bis‐acrylate and conventional PMMA found in this study are in agreement with previous studies . Karaokutan et al evaluated the fracture strength of seven interim crown materials after 5000 thermocycles.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Therefore, direct comparison to other studies is not possible. The improved FS of CAD/CAM PMMA‐based polymers compared to bis‐acrylate and conventional PMMA found in this study are in agreement with previous studies . Karaokutan et al evaluated the fracture strength of seven interim crown materials after 5000 thermocycles.…”
Section: Discussionsupporting
confidence: 91%
“…Higher FS is essential for achieving clinical success with interim prostheses. Parallel with the results of the current study, in previous studies, bis‐acrylate composite resin had higher FS than conventional PMMA resins . Balkenhol et al evaluated the FS of different interim resins at different storage times after mixing, and reported that the FS of the materials are dependent on the storage time.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations